How attitudes and purchases differ between also-online versus offline-only grocery shoppers in online and offline grocery shopping - Philipp Brüggemann; Koen Pauwels (Electronic Commerce Research, 2024)
The surge in online grocery shopping amid the COVID-19 pandemic has significantly altered the balance between offline and online purchases, influencing consumer attitudes toward these channels. Given the anticipated continued growth of online grocery shopping in the coming years, research on this topic becomes increasingly crucial for retailers, manufacturers, and consumers. Particularly, brand managers and retailers find themselves uncertain about the implications for their consumer segments and products, including national versus private label brands, organic products, and fair-trade products. Against this backdrop, our study delves into consumer characteristics and purchase behavior to explore the distinctions between offline-only and also-online grocery shoppers. Additionally, we examine whether consumer behavior varies across offline and online channels. Specifically, we analyze extensive household panel data encompassing 4,142,485 purchases and diverse consumer characteristics (such as demographics and attitudes) from an average of 21,428 households spanning the years 2016–2020. It is noteworthy that also-online shoppers, despite their preference for convenience, tend to be younger, reside in larger cities, and exhibit more positive attitudes toward buying local and environmental responsibilities. These consumers, characterized by lower price consciousness and higher brand preferences, display a greater inclination toward national brands online compared to offline. Furthermore, they express more favorable attitudes toward organic and fair-trade products and exhibit relatively higher purchasing of these items. Our extensive empirical analyses reveal that these cross-sectional differences are attributable, in part, to demand-driven factors and, in part, to supply-side effects. Through this research, we provide valuable insights to brand managers, retailers, and researchers, facilitating a better understanding of the evolving retail landscape, particularly within the dynamic realm of online grocery shopping.
Keywords: 380; E-commerce; Consumer attitudes; Consumer behavior; Grocery shopping; Online grocery shopping; Online shopping; Retail